Molecular architecture and microporous structure of low mature lacustrine kerogen: A multi-parameter modeling of the Triassic Yanchang Formation, Ordos Basin - Yinhai Song; Meijun Li; Xiaoqiang Liu; Xia Luo; Qingyong Luo; Qingbin Xie; Haochen Chen; Zhihao Wang (Fuel, 2027)

Fruit allergens and their allergenicity reduction: characteristics, technologies, and prospects - Tanying Zhang; Jinshen Chu; Yuntong Ying; Haochen Ye; Mengxian Li; Yiran Xie; Haozhe Yi; Jing Che; Bowen Li; Binjia Zhang; Xiaowen Pi (Trends in Food Science & Technology, 2026)

Three-dimensional printed zerovalent iron enables selective and sustained reductive dehalogenation of florfenicol via structure-induced corrosion resistance and electron transfer regulation - Dan Li; Lu Liu; Haochen Li; Tao Ye; Junhong Wu; Jiaying Li; Si Zhai; Mengli Li; Huigai Wei; Lei Li; Jianhui Xu; Peng Liu; et al. (Environmental Research, 2026)

Secondary growth enables post-healing of stress-induced cracks in 2D Zr-MOF membrane for enhanced water purification - Miaomiao Tian; Haochen Shen; Cheng Chen; Libo Zhao; Wei Yu; Bisheng Li; Leihong Zhao; Hongjun Lin; Liguo Shen (Chemical Engineering Journal, 2026)

End-of-life allocation shapes carbon accounting and technology appraisal in life cycle assessment of electric vehicles across multi-generation cascades - Ziang Liu; Guangming Li; Haochen Zhu; Haoyuan Deng; Wenzhi He (Waste Management, 2026)

Eco-friendly fluidized solidified loess incorporating multi-source industrial solid wastes: A systematic study from rheological features, mechanical performance, and stabilization mechanisms - Baofeng Lei; Jucong Sun; Henghui Fan; Yongxiang Cao; Changhao Liu; Haochen Zhang; Shuai Pang; Jiaze Li; Huihui Yu; Minqiang Meng (Process Safety and Environmental Protection, 2026)

A numerical study of the possible influence of the ice nucleation process on the bolt-from-the-blue lightning production - Qianwei Zhao; Zheng Shi; Yanfeng Fan; Xuedong Cui; Haochen Chen; Wenzhong Li (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Proteomic insights into the combined effects of near-threshold bleaching temperature and prometryn exposure on the coral Galaxea fascicularis - Sichen Li; Yanyu Zhou; Haochen Niu; Weilu Kang; Guowei Fu; Bo Hu; Hongwei Zhao (Marine Environmental Research, 2026)

Hydrogen radical is also a critical reductive defluorination species in the Far-UVC-activated sulfite process - Xiangyang Hou; Shu Xu; Qiuling Lu; Kai Wang; Haonan Lu; Haochen Zhang; Yuying Li; Minchao Liu; Jin Jiang; Shuo Li; Jun Ma; Tiangang Luan; et al. (Journal of Hazardous Materials, 2026)

Solar light irradiation activated dichloramine for efficient abatement of micropollutants - Peng Su; Wenjun Zhang; Haochen Zhang; Haonan Lu; Qiuling Lu; Kai Wang; Yuying Li; Xiaolong Xu; Changyu Liu; Jun Ma; Tao Yang (Water Research, 2026)

Supramolecular nanomedicine reprogramming calcium ions metabolism for cancer cell PANoptosis and immunotherapy - Yongjuan Li; Danyang Shen; Xianlong Zong; Furu Gong; Xinran Zhu; Jiajia Wu; Hongfei Xue; Haochen Yao; Rui Li (Science Bulletin, 2026)

Occurrence, seasonal variability, and ecological risk of emerging contaminants in estuarine and nearshore waters around Hainan Island, China - Haochen Niu; Yuehua Huang; Sichen Li; Xueqing Zhou; Chuhan Sun; Hongwei Zhao (Marine Environmental Research, 2026)

Recovery of silver and silicon from spent solar cells by direct separation driven by galvanic and chemical etching in molten chloride - Haochen Wang; Hongya Wang; Shiyu Wang; Yubo Zhou; Danfeng Wang; Fengyin Zhou; Xinyi Li; Junmin Peng; Xiang Chen; Dihua Wang; Huayi Yin (Science Bulletin, 2026)

Lighting up the Arctic: Nighttime light data reveals economic growth in the north in Norway, Sweden and Finland - Zhenfu Li; Haochen Yu; Chunrui Song; Xinli Qi; Qiqi Zhang (Polar Science, 2026)

A recyclable and self-supporting spinel anode for electrochemical activation of peroxymonosulfate to sulfamethoxazole degradation - Wentao Qiu; Hao Shi; Mengyi Tang; Xiaodan Zhang; Haochen Wang; Wei Li; Dihua Wang (Journal of Environmental Chemical Engineering, 2026)

Effects of nitrogen, phosphorus and potassium fertilizers on trace element accumulation and greenhouse gas emissions in a rice-vegetable rotation system - Jie Zhang; Bo Gao; Xingfeng Zhang; Junjiang Li; Junjie Huang; Haochen Yu (Plant and Soil, 2026)

Optimizing regional nitrogen management for intensive rice systems: A machine learning-based framework for reconciling agronomic nitrogen demands with environmental constraints - Zenghui Liang; Zhongwei Li; Haochen Li; Qiang Cao; Yongchao Tian; Yan Zhu; Weixing Cao; Zhaopeng Fu; Xiaojun Liu (Agricultural Systems, 2026)

The influence of potassium ions on CuMgAlOx catalysts during hydrodeoxygenation of biomass pyrolysis oil - Zhongxi Jiang; Mingyue Yang; Xiaowei Bai; Haochen Yang; Zhenghua Dai; Yunpeng Zhao; Jian Li (Biomass and Bioenergy, 2026)

A review of tree nut allergens and their processing for decreasing allergenicity - Haochen Ye; Tanying Zhang; Siyu Ren; Jingwei Jiang; Zeyu Peng; Jia Cao; Jinshen Chu; Bowen Li; Haozhe Yi; Binjia Zhang; Huan Wang; Xiaowen Pi (Trends in Food Science & Technology, 2026)

Why same datasets yield different environment–activity relationships? Hidden uncertainties in geospatial processing methods - Haochen Shi; Lingzi Xu; Ding Ma; Feng Gao; Shaoying Li (Computers, Environment and Urban Systems, 2026)

Patterns and causes of ammonia nitrogen enrichment in groundwater of a typical agricultural irrigation area in the northern Henan Plain, China - Haoyang Li; Liang Zhang; Mingming Luo; Xiaoyang Liu; Gaoxin Xiao; Ruihua Shang; Shuna Sun; Haochen Gu; Chengyi Zu (Environmental Geochemistry and Health, 2026)

Characterization of Interlayer Resistivity Responses in Crack-Containing Rock-Like Materials and Analysis of Failure Precursors - Tingye Qi; Hongtao Xu; Guorui Feng; Tian Qiu; Haochen Wang; Linfei Wang; Siyuan Cheng; Xinkai Qi; Lubin Li (Rock Mechanics and Rock Engineering, 2026)

Evolutionary game analysis of pirate attack based on prospect theory - Zhenfu Li; Haochen Yu; Xinli Qi; Chunrui Song; Wei Duan; Shiyue Li (Frontiers in Marine Science, 2026)
Pirate attacks are related to shipping safety, international trade order, and regional political stability. How to effectively address this problem has become a pressing issue that the international community needs to tackle urgently. This study constructs a three-player evolutionary game model involving shipping companies, pirates, and the government. It analyzes the strategic evolution and interaction mechanisms of each subject in the context of pirate attacks. Based on prospect theory, this study employs MATLAB simulation experiments and sensitivity analysis to investigate the impact of subjective factors, such as risk aversion, on the strategic choices of each player. The results show that: (1) The key to effectively curbing piracy is to increase the intensity of crackdowns on its crimes to reduce its illegal profit expectations; (2) Shipping companies show a strong risk aversion tendency in the game, and they tend to equip defensive equipment even if the probability of pirate attacks is very low; (3) The government’s perceived value sensitivity coefficient threshold is the highest. Only when it has a stronger risk perception and strategy adjustment capabilities can it adjust its escort policy promptly in response to pirate attacks. This study can provide theoretical support and decision-making reference for the formulation of quantitative representation of cross-border governance modesce policies.

Mechanobiological Response of Osteocyte TRPV4 Base on the Piezoelectricity of Bone Matrix - Shibo Gu; Yuqing Duanwang; Yinuo Zhao; Shuo Gao; Haochen Li; Xinrui Wu; Quanyou Zhang; Yanru Xue; Meng Zhang; Xiaogang Wu; Weiyi Chen (Annals of Biomedical Engineering, 2026)

Study on oxidation kinetics and evolution mechanism of key microcosmic group in symbiotic coal-oil systems - Yutao Zhang; Haodong Yang; Yuanbo Zhang; Yaqing Li; Qiang Guo; Haochen Li; Gang Zhou; Junwu Zhang; Wei Huang (Fuel, 2026)

From behavior to taste: Developmental trajectories of anxiety-like phenotypes unveil a neuroendocrine link to flesh quality in economic crustaceans - Hengtong Liu; Sisi Sheng; Yiming Li; Wanting Huang; Wenbin Liu; Haochen Wang; Cheng Chi; Dingdong Zhang (Food Bioscience, 2026)

CitrusNet: A vision transformer-CNN approach for citrus detection from multi-source imagery with multi-scale feature integration - Haochen Wang; Juan Shi; Hamed Karimian; Fei Wang; Faizan Javed; Bo Liu; Shengnan Shi; Ziwei Li; Yang Tao (Computers and Electronics in Agriculture, 2026)

Mobile MAX-DOAS measurements and source analysis of NO2, HCHO, and HONO during the Chengdu 2023 FISU world university games - Qijin Zhang; Chengzhi Xing; Miao Feng; Yinshuo Ding; Zhongmou Sun; Yikai Li; Haochen Peng; Wei Tan; Zhiguo Zhang; Tianjun Du; Cheng Liu (Journal of Environmental Sciences, 2026)

A green approach for the selective recovery of Copper, Lead, and Tin from End-of-Life photovoltaic solder ribbons - Shun Dai; Shiyu Wang; Haochen Wang; Fengyin Zhou; Simin Xu; Yongxin Wu; Muya Cai; Xinyi Li; Shuaibo Gao; Wei Li; Bowen Deng; Dihua Wang; et al. (Waste Management, 2026)

A comparative study on the occurrence and pore structure characteristics of CH4 and CO2 hydrates in sandy sediments using SEM-EDS technology - Lujun Wang; Haochen Yang; Chuanqi Sun; Jianye Sun; Xiluo Hao; Chengfeng Li; Bin Zhu; Yunmin Chen (Gas Science and Engineering, 2026)

Close-packed metal organic frameworks enabled high-energy solid-state lithium metal batteries - Yining Zhang; Hongsheng Shi; Yuyao Zhang; Xin Chen; Shuanghong Wang; Jinjiang Liang; Qiong Yuan; Tianyi Gao; Ran Wei; Haochen Zhang; Tao Li; Tianquan Lin; et al. (Chemical Engineering Journal, 2026)

Effectiveness of MTMD for jacket offshore platform under wave and earthquake excitations - Shutong Liu; Xunhe Yin; Haochen Li; Jingchao Yang; Peizhen Li; Peng Li (Soil Dynamics and Earthquake Engineering, 2025)

Effect of offshore fixed photovoltaic pile foundations on wave fields: A theoretical study - Haochen Zhang; Gao Li; Jing Geng; Xuanlie Zhao (Ocean Engineering, 2025)

Nanoplastic-mediated disruption of freshwater carbon cycling via modulating of plankton communities - Peng Wang; Haochen Yang; Chengjing Li; Zihao Fu; Qianqian Xiang; Xia Luo; Liqiang Chen (Journal of Hazardous Materials, 2025)

Pore-scale simulation of oil-water flow in shale media after fracture hits: an integrated approach using U-net and lattice Boltzmann method - Peiyu Li; Yilei Song; Jiatong Jiang; Zhaojie Song; Xiao Han; Xiukun Wang; Haochen Ren; Jixiang He (Fuel, 2025)

Assessing the effect of a non-ionic surfactant on surface degradation of the pesticide Acetamiprid on live tea plants - Wanjun Gao; Xinyi Du; Zili Gao; Haochen Dai; Lanying Li; Bingling Zhang; Gaoxi Wang; Xuejuan Chen; Jeffery Doherty; John M. Clark; Ruyan Hou; Fan Luo; et al. (Food Research International, 2025)

Recent advances of high-intensity ultrasound on protein structure and quality: Allergenicity, physicochemical properties, functionality assessment and future perspective - Xiaowen Pi; Haochen Ye; Qingqing Cao; Yijia Jia; Yi Chen; Chunyan Bo; Bowen Li; Jinshen Chu (Food Chemistry, 2025)

Corrigendum to “A review of wheat allergy: allergens characteristic, the impact of processing on allergenicity and future perspective” [Trends in Food Science & Technology 164 (2025) 105244] - Xiaowen Pi; Siyu Ren; Haochen Ye; Jia Cao; Jinshen Chu; Lingling Cao; Bowen Li; Binjia Zhang (Trends in Food Science & Technology, 2025)

Exploring the recreational micromobility in relation to historic urban areas and social media: Insights from machine learning approaches - Hao Huang; Haochen Shi; Xinjian Li; Yankai Wang (Landscape and Urban Planning, 2025)

Multi-cation system in spent lithium-ion batteries leaching solution: a pathway to lithium-selective via nanofiltration - Zihan Xu; Chunchun Meng; Yanhui Wu; Xinwu Li; Xinyu Zeng; Guangming Li; Haochen Zhu (Desalination, 2025)

A review of wheat allergy: allergens characteristic, the impact of processing on allergenicity and future perspective - Xiaowen Pi; Siyu Ren; Haochen Ye; Jia Cao; Jinshen Chu; Lingling Cao; Bowen Li; Binjia Zhang (Trends in Food Science & Technology, 2025)

Enhanced degradation of tetracycline over the novel biochar doped with Cu-Mn by peroxymonosulfate activation: Performance evaluation and mechanisms - Xinyu Li; Haochen Li; Xiaofei Zong; Yanbo Wang; Jiahui Wu; Yuwei Deng; Yuxuan Ye; Wentao Li; Qiang Li; Fei Pan (Journal of Environmental Chemical Engineering, 2025)

Construction of efficient proton channels with silica-encapsulated carbon nanotubes for proton exchange membrane water electrolysers - Min Huang; Yang Li; Haochen Lu; Siyi Gao; Felix Kwofie; Xinyao Guo; Quentin Meyer; Yi Wang; Chuan Zhao; Nanwen Li; Yi Cheng (Chemical Engineering Journal, 2025)

Impact of biochar on the fate of 15N-labelled fertilizer in water-saving and flooding irrigated rice-soil system under three different nitrogen sources - Xi Chen; Zhihui Wang; Ningbo Cui; Li Guo; Kangning Yu; Haochen Jin; Shikuan Sun (Plant and Soil, 2025)

Efficient permanganate activation under UV 222 nm irradiation for enhanced pollutant abatement - Haochen Zhang; Peng Su; Maoju Jiang; Chenlong Liu; Qixiao Lv; Wenqi Li; Xiangyang Hou; Junhui Zhou; Shuo Li; Bin Zhang; Bei Zhang; Jun Ma; et al. (Water Research, 2025)

High-touch surfaces with moderate contamination levels as key nodes in microbial dissemination - Pengcheng Zhao; Peihua Wang; Tzehau Lam; Nan Zhang; Huanhuan Wang; Haochen Zhang; Jiquan Liu; Yuguo Li (Journal of Hazardous Materials, 2025)

Cigarette smoke-induced PPAR signaling dysregulation accelerates Alzheimer's disease pathogenesis and cognitive decline in 5xFAD mice - Yunqi Xie; Haochen Wang; Yajie Zhang; Bingbing Lin; Yuting Chen; Kai Li; Huanwen Tang; Qian Sun (Food and Chemical Toxicology, 2025)

Optimizing performance and stability in textured 2 T perovskite/silicon tandem photovoltaic devices through self-assembled monolayer-mediated doping strategies - Rui Li; Jungan Wang; Huiwei Du; Chenghao Song; Haochen Zhang; Menglei Xu; Peiting Zheng; Xinyu Zhang; Jie Yang; Chengjun Gu; Qin Zou; Jingji Zhang; et al. (Chemical Engineering Journal, 2025)

Spatiotemporal variability of soil moisture and its influencing factors in a forested catchment with complex terrain - Haochen Liu; Shangqiang Hui; Yuting Zhao; Yanjia Jiang; Yongliang Qi; Elizabeth W. Boyer; Carlos R. Mello; Li Guo; Hongxia Li (CATENA, 2025)

Icing monitoring technology and application of 10 kV overhead distribution lines based on axial tension measurement - Lin Yang; Lulu Mei; Haochen He; Quan Liu; Yanpeng Hao; Licheng Li; Xinhao Lin (Cold Regions Science and Technology, 2025)

Silver nanoparticles alter plankton-mediated carbon cycle processes in freshwater mesocosms - Peng Wang; Qianqian Xiang; Zihao Fu; Chengjing Li; Haochen Yang; Jun Zhang; Xia Luo; Liqiang Chen (Journal of Hazardous Materials, 2025)

Advances of Complex Marine Environmental Influences on Underwater Vehicles - Sen Zhao; Haibao Hu; Abdellatif Ouahsine; Haochen Lu; Zhuoyue Li; Zhiming Yuan; Peng Du (Journal of Marine Science and Engineering, 2025)
Underwater vehicles serve as critical assets for global ocean exploration and naval capability enhancement. The marine environment exhibits intricate hydrodynamic phenomena that significantly threaten underwater vehicle navigation safety, particularly in four prevalent complex conditions: surface waves, oceanic currents, stratified fluids, and internal waves. This comprehensive review systematically examines the impacts of these four marine environments on underwater vehicles through critical analysis and synthesis of contemporary advances in theoretical frameworks, experimental methodologies, and numerical simulation approaches. The identified influences are categorized into five primary aspects: hydrodynamic characteristics, dynamic response patterns, load distribution mechanisms, navigation trajectory optimization, and stealth performance. Particular emphasis is placed on internal wave interactions, with rigorous analysis derived from experimental investigations and numerical modeling of internal wave dynamics and their coupling effects with underwater vehicles. In addition, this review points out and analyzes the shortcomings of the current research in various aspects and puts forward some thoughts and suggestions for future research directions that are worth further exploration, including enriching the research objects, upgrading the experimental techniques, and introducing artificial intelligence methods.

Ocean mixed layer depth 2000–2020: Estimation assessment and long-term trends - Haochen Tang; Chen Wang; Huimin Li; Yijun He (Progress in Oceanography, 2025)

Mechanism of reducing antibiotic resistance genes by nano-selenium during composting: insight into host microorganisms and a two-component system - Xi Chen; Muqing Zhan; Haochen Shao; Shuangshuang Ma; Li Liu; Zuyong Chen; Chen Fang (Journal of Environmental Management, 2025)

Shaddock peels biochar doping with Fe-Co bimetal for peroxymonosulfate activation on the degradation of tetracycline: The influence of HCO3− and PO43− - Haochen Li; Jiahui Wu; Ao Ren; Yao Qu; Xiaofei Zong; Yaoyao Gong; Dandan Wang; Yuxuan Ye; Qiang Li; Zhenbin Wu; Fei Pan (Environmental Research, 2025)

Light-enhanced ion transport and fouling resistance properties of metal/semiconductor heterojunction nanochannel membranes for osmotic energy recovery in real-world conditions - Haochen Lu; Jin Wang; Derong Zhang; Tongxin Liao; Shangzhen Li; Lei Lei; Zhiyan Liu; Bingjie Du; Xudong Wang; Lei Wang (Water Research, 2025)

AI-Driven urban planning optimization: A graph neural network and genetic algorithm framework for tackling peak-hour challenges - Jianyi Li; Yin Zhang; Shuo Yu; Haochen Qin; Zhen Xu (Sustainable Cities and Society, 2025)

Phosphorus addition mitigates the combined negative effects of high temperature and nitrogen stress on corals - Zhuojing Zhou; Huidan Yang; Sichen Li; Haochen Niu; Dongdan Yuan; Hongwei Zhao (Marine Environmental Research, 2025)

Ultra-low Pt induced amorphous/crystalline heterophase Pt-Co2P hollow nanotubes for superior water electrolysis at industrial temperatures - Ziting Li; Peng Zhou; Mingyan Zhang; Haochen Zhang; Yongyi Zhang; Dan Han; Xiaoshuang Chen (Fuel, 2025)

Thermokinetic analysis of surface-active groups in coal using ultrasonic extraction method - Yaqing Li; Xinxin Sun; Yutao Zhang; Jun Deng; Kexin Liu; Yuanbo Zhang; Qiang Guo; Haochen Li (Fuel, 2025)

Hydrogel-based materials for microbial/enzyme immobilization: Advanced applications in wastewater treatment - Haochen Hu; Wenxin Lu; Shipeng Li; Xingkun Zhou; Chengyuan Zhu; Xingang Wang; Hongliang Dai; Hongya Geng (Chemical Engineering Journal, 2025)

Mode transitions in Hall effect thrusters by Varying duty ratio under pulsating operation - Haochen Ma; He Zheng; Tiance Liang; Jiapeng Li; Liqiu Wei; Liang Han; Hong Li; Yongjie Ding (Advances in Space Research, 2025)

Facility of tomato plant organ segmentation and phenotypic trait extraction via deep learning - Jiangjun Yao; Yan Gong; Zhengyan Xia; Pengcheng Nie; Honggang Xu; Haochen Zhang; Yufei Chen; Xuehan Li; Zhe Li; Yiming Li (Computers and Electronics in Agriculture, 2025)

Comparative transcriptome analyses reveal the acute heat stress response of a cool-temperate shrimp Fenneropenaeus chinensis - Haochen Zhu; Xiaojun Zhang; Xiaoxi Zhang; Jianbo Yuan; Zhenxia Sha; Fuhua Li (Journal of Thermal Biology, 2025)

In-situ constructed ZnAl2O4/A-MoS2 Z-scheme heterojunction for visible-light-thermo cascade catalytic CO2 cycloaddition - Congcong Zhang; Bin Jiang; Runjia Mou; Haochen Shen; Qi Zhou; Longfei Zhang; Jingshuai Li; Na Yang; Luhong Zhang (Journal of Environmental Chemical Engineering, 2025)

Study on the characteristics of nanocomposite hydrogels loaded with piceatannol to inhibit coal spontaneous combustion - Yutao Zhang; Xinzu Jin; Tianyang Deng; Yuanbo Zhang; Shangwen Xia; Haochen Li (Fuel, 2025)

The relationship between high-quality development and ecosystem health in China's urban agglomerations - Bin Yang; Xiaohan Ma; Jirong Li; Haochen Yu; Hongjun Sui; Fu Chen; Li Tan (Journal of Environmental Management, 2025)

Investigation on the rejection of mixed salt solution by g-C3N4 functionalized nanofiltration membrane - Zihan Xu; Zhaohuan Mai; Yanhui Wu; Xinwu Li; Xinyu Zeng; Chunchun Meng; Guangming Li; Haochen Zhu (Desalination, 2025)

Transmission of respiratory diseases in high-metabolic environments: A case study of gym - Haochen Zhang; Pengcheng Zhao; Zhiyang Dou; Boni Su; Yuguo Li; Nan Zhang (Building and Environment, 2025)

Facile formation of van der Waals metal contact with III-nitride semiconductors - Xiyu Sun; Danhao Wang; Xiaojing Wu; Jiahao Zhang; Yangjian Lin; Dongyang Luo; Fang Li; Haochen Zhang; Wei Chen; Xin Liu; Yang Kang; Huabin Yu; et al. (Science Bulletin, 2024)

Shaking table test and numerical simulation of jacket offshore platform considering soil-water-structure interaction - Shutong Liu; Haochen Li; Jin Zhang; Shutong Yang; Tianyu Zhang (Ocean Engineering, 2024)

A study of wave forces on a vertical truncated cylinder with different submergence depths - Yuping Fan; Jinxuan Li; Shuxue Liu; Haochen Zhang (Ocean Engineering, 2024)

Human behavior-based COVID-19 transmission in two dining spaces - Zhikang Xu; Haochen Zhang; Min Zhu; Ying Ji; Peng Xue; Jingchao Xie; Yuguo Li; Nan Zhang (Journal of Hazardous Materials, 2024)

Effectiveness of composite fume suppression and deodorizing agents in improving performance and reducing emissions of rubber modified asphalt - Juan Xie; Zheyu Ding; Haochen Luo; Zhenzhen Lu; Shuaihui Li; Xucheng Zhao; Bin Huang; Jinmei Lin (Journal of Cleaner Production, 2024)

A disposable microfluidic aptasensor for one-step and real-time detection of sub-femtomolar-level aflatoxin B1 in food - Haochen Qi; Jian Zhang; Xueyong Zhang; Li Lv; Tianqi Wang; Erhui Huang; Jayne Wu; Lei Zheng (Food Research International, 2024)

Copper-doped orange peel biochar activated peroxydisulfate for efficient degrading tetracycline: The critical role of C-OH and Cu - Haochen Li; Haochao Sun; Qiang Li; Xiaofei Zong; Longli Wu; Zhengyu Han; Xinyu Li; Jiahui Wu; Yuxuan Ye; Fei Pan (Environmental Research, 2024)

Enhanced peracetic acid activation under Far-UVC Radiation: Micropollutant degradation and radical assessment - Tao Yang; Maoju Jiang; Peng Su; Qixiao Lv; Wenqi Li; Chenlong Liu; Bin Zhang; Haochen Zhang; Linlin Zang; Minchao Liu; Jun Ma (Chemical Engineering Journal, 2024)

Study on high-temperature emission behaviors of crumb rubber modified asphalt: Experimental analysis and molecular simulation approach - Juan Xie; Zheyu Ding; Haochen Luo; Shuaihui Li; Wen He; Xucheng Zhao; Yuetan Ma (Journal of Cleaner Production, 2024)

Preparation of polyethylene based composite nanofiltration membrane and its application in removal of heavy metals for water purification - Lin Wang; Guiru Zhu; Haochen Ge; Yunbo Tong; Lingling Li; Ziqi Wang; Congjie Gao (Desalination, 2024)

Machine Learning-Driven Precise Design of Stable OLED Materials: Predicting and Enhancing Multi-State C-N Bond Dissociation Energies - Yiming Shi; Haochen Shi; Haichang Wang; Chun-Jung Chen; Yaoyao Li; Bo Qiao; Zhiqin Liang; Suling Zhao; Deyu Hang; Zheng Xu; Dandan Song (Chemical Engineering Journal, 2024)

Differential impacts of microplastics on carbon and nitrogen cycling in plant-soil systems: A meta-analysis - Yige Liu; Siyi Chen; Pengyu Zhou; Haochen Li; Quan Wan; Ying Lu; Bo Li (Science of The Total Environment, 2024)

Experimental and numerical analysis of wave forces on a vertical truncated cylinder with different depths of submergence under focused waves - Yuping Fan; Jinxuan Li; Shuxue Liu; Haochen Zhang (Ocean Engineering, 2024)

In-situ repair of failed LiFePO4 cathode using residual Li- and C-containing impurities from active material separation process - Ben Wang; Yanwei Yin; Haoyuan Deng; Guangming Li; Haochen Zhu; Wenzhi He (Chemical Engineering Journal, 2024)

Gel beads prepared by polyvinyl alcohol cross-linking with phytic acid and Fe as novel microbial carriers for simultaneous partial nitrification, anammox and denitrification - Deyuan Jin; Wenqing Tian; Wuke Guo; Haochen He; Jidong Liang; Hua Ji; Xiaofeng Li; Dangyong Li; Pengkang Jin (Bioresource Technology, 2024)

Relying on free radical degradation of cephalexin by novel Cu1Co2@C catalyzed by permonosulfate: Mechanism and degradation pathways - Xiaofei Zong; Xinyu Li; Jiahui Wu; Xi Ni; Haochen Li; Zhengyu Han; Rongling Wang; Yuwei Deng; Yuxuan Ye; Lei Sun; Qiang Li; Fei Pan (Journal of Water Process Engineering, 2024)

Interaction of composite fume suppression and odor elimination agents with crumb rubber modified asphalt: Inhibition behavior of volatile organic compounds (VOCs) and inorganic fume - Juan Xie; Zheyu Ding; Haochen Luo; Xucheng Zhao; Shuaihui Li; Yuetan Ma (Science of The Total Environment, 2024)

Dietary flavonoids modulate the gut microbiota: A new perspective on improving autism spectrum disorder through the gut-brain axis - Haochen Dai; Yuhan Jiang; Shuxun Liu; Dandan Li; Xin Zhang (Food Research International, 2024)

Carbon slow-release and enhanced nitrogen removal performance of plant residue-based composite filler and ecological mechanisms in constructed wetland application - Zhaoyang Li; Tianyin Huang; Wei Wu; Xiaoyi Xu; Bingdang Wu; Jinlong Zhuang; Jingjing Yang; Haochen Shi; Yang Zhang; Bin Wang (Bioresource Technology, 2024)

Studies on regional ozone formation sensitivities and transport with higher spatiotemporal resolutions in a stereoscopic dimension: GEMS and vertical observations - Haochen Peng; Chengzhi Xing; Yikai Li; Chengxin Zhang; Jinan Lin; Jingkai Xue; Xiaohan Wang; Yuhang Song; Xinhan Niu; Cheng Liu (Atmospheric Research, 2024)

State-Transform MPC-SMC-Based Trajectory Tracking Control of Cross-Rudder AUV Carrying Out Underwater Searching Tasks - Haochen Hong; Zhiqiang Yang; Jiawei Li; Guohua Xu; Yingkai Xia; Kan Xu (Journal of Marine Science and Engineering, 2024)
In this study, we present a novel dual-loop robust trajectory tracking framework for autonomous underwater vehicles, with the objective of enhancing their performance in underwater searching tasks amidst oceanic disturbances. Initially, a real-world AUV experiment is conducted to validate the efficacy of a cross-rudder AUV configuration in maintaining sailing angle stability during the diving stage, which exhibits a strong capability for straight-line sailing. Building upon the experimental findings, we introduce a state-transform-model predictive guide law to compute the desired velocity for the dynamics loop. This guide law dynamically adjusts the controller across varying depths, thereby reducing model predictive control (MPC) computation while optimizing timing without compromising precision or convergence speed. Subsequently, we incorporate a sliding mode controller with a prescribed disturbance observer into the velocity control loop to concurrently enhance the robustness and convergence rate of the system. This innovative amalgamation of controllers significantly improves tracking precision and convergence rate, while also alleviating the computational burden—a pervasive challenge in AUV MPC control. Finally, various condition simulations are conducted to validate the robustness, effectiveness, and superiority of the proposed method. These simulations underscore the enhanced performance and reliability of our proposed trajectory tracking framework, highlighting its potential utility in real-world AUV applications.

Glowing and flaming autoignition of wood exposed to coupled convective and radiative heating - Junhui Gong; Hu Lin; Tong Cui; Haochen Lian; Lun Li; Kun Zhao (Fuel, 2024)

Diversity of heat shock proteins in response to various stressors in the Pacific white shrimp Litopenaeus vannamei - Xiaoxi Zhang; Haochen Zhu; Jianbo Yuan; Xiaojun Zhang; Jianhai Xiang; Fuhua Li (Aquaculture, 2024)

The pyrolysis of 4,4,8,10-tetramethyl decalin and the influence of molecular structures on oil thermal cracking: A ReaxFF molecular dynamics simulation and DFT study - Haochen Chen; Meijun Li; Xiaoqiang Liu; Qiuya Han; Wenke Li; Siyuan Zhang (Fuel, 2024)

Operator learning for urban water clarification hydrodynamics and particulate matter transport with physics-informed neural networks - Haochen Li; Mohamed Shatarah (Water Research, 2024)

One-step strategy for efficient Cr(VI) removal via phytate modified zero-valent iron: Accelerated electron transfer and enhanced coordination effect - Rui Gan; Yuxuan Ye; Ziyi Zhan; Qiuyue Zhang; Yuwei Deng; Yingjie Liu; Haochen Li; Jun Wan; Xuanyuan Pei; Qiang Li; Fei Pan (Journal of Hazardous Materials, 2024)

A new ternary diagram to decipher the evolution of maturity and biodegradation of crude oil using ESI FT-ICR MS - Dongyong Wang; Meijun Li; Jianfa Chen; Haochen Chen; Quan Shi (Fuel, 2024)

Highly efficient adsorption of ciprofloxacin from aqueous solutions by waste cation exchange resin-based activated carbons: Performance, mechanism, and theoretical calculation - Qiang Li; Haochen Li; Xiaofei Zong; Haochao Sun; Yunhao Liu; Ziyi Zhan; Shou Mei; Yanjie Qi; Yangbo Huang; Yuxuan Ye; Fei Pan (Science of The Total Environment, 2024)

Research on the operation strategy of joint wind-photovoltaic-hydropower-pumped storage participation in electricity market based on Nash negotiation - Xudong Li; Zhongfu Tan; Junyao Shen; Jiacheng Yang; Wei Fan; Haochen Zhao; Ting Zhang (Journal of Cleaner Production, 2024)

Separation performance of graphene oxide nanofiltration membrane intercalated by MWCNTs and α -Fe2O3 nanoparticles - Baowen Liang; Han Hu; Haochen Zhu; Yunhan Yu; Wenzhi He; Guangming Li (Science of The Total Environment, 2024)

An artificial neural network-based machine learning approach to correct coarse-mesh-induced error in computational fluid dynamics modeling of cell culture bioreactor - Fernando José Cantarero-Rivera; Ran Yang; Haochen Li; Hairong Qi; Jiajia Chen (Food and Bioproducts Processing, 2024)

Long-term observations of NO2 using GEMS in China: Validations and regional transport - Yikai Li; Chengzhi Xing; Haochen Peng; Yuhang Song; Chengxin Zhang; Jingkai Xue; Xinhan Niu; Cheng Liu (Science of The Total Environment, 2023)

The biological source and paleoenvironment implication of rare short-chain lanostanes in alkaline lacustrine sediments - Dongyong Wang; Meijun Li; Jianfa Chen; Hong Xiao; Xianli Zou; Lu Yang; Haochen Chen; Huiqiang Qin (Organic Geochemistry, 2023)

Efficient HCl leaching of platinum group metals from waste three-way catalysts: A study on kinetics and mechanisms - Shiqiang Sun; Wenting Zhao; Chenxi Jin; Wenzhi He; Guangming Li; Haochen Zhu (Environmental Research, 2023)

A lightweight deep learning model for ocean eddy detection - Haochen Sun; Hongping Li; Ming Xu; Fan Yang; Qiang Zhao; Cuishu Li (Frontiers in Marine Science, 2023)
Ocean eddies are typical oceanic mesoscale phenomena that are numerous, widely distributed and have high energy. Traditional eddy detection methods are mainly based on physical mechanisms with high accuracy. However, the large number of steps and complex parameter settings limit their applicability for most users. With the rapid development of deep learning techniques, object detection models have been broadly used in the field of ocean remote sensing. This paper proposes a lightweight eddy detection model, ghost eddy detection YOLO (GED-YOLO), based on sea level anomaly data and the “You Only Look Once” (YOLO) series models. The proposed model used ECA+GhostNet as the backbone network and an atrous spatial pyramid pooling network as the feature enhancement network. The ghost eddy detection path aggregation network was proposed for feature fusion, which reduced the number of model parameters and improved the detection performance. The experimental results showed that GED-YOLO achieved better detection precision and smaller parameter size. Its mAP was 95.11% and the parameter size was 22.56 MB. In addition, the test experiment results showed that GED-YOLO had similar eddy detection performance and faster detection speed compared to the traditional physical method.

The fate of microplastic pollution in the Changjiang River estuary: A review - Yifei Li; Qingbing Lu; Jian Yang; Yi Xing; Wei Ling; Kai Liu; Qizhen Yang; Hongjie Ma; Zengxin Pei; Tianqi Wu; Haochen Guo; Ziyuan Gao; et al. (Journal of Cleaner Production, 2023)

Mitogenome analysis reveals predominantly ancient Yellow River origin of population inhabiting Datong agro-pastoral ecotone along Great Wall - Yuqing Yan; Panxin Du; Jihong Zhang; Ruilan Li; Haoquan Bao; Qingli Fang; Ye Gao; Hailiang Meng; Yiran Xu; Haochen Shi; Hailong Yan; Xin Chang; et al. (Molecular Genetics and Genomics, 2023)

Research on Black Smoke Detection and Class Evaluation Method for Ships Based on YOLOv5s-CMBI Multi-Feature Fusion - Shipeng Wang; Yang Han; Mengmeng Yu; Haiyan Wang; Zhen Wang; Guangzheng Li; Haochen Yu (Journal of Marine Science and Engineering, 2023)
To enhance the real-time detection accuracy of ship exhaust plumes and further quantify the degree of darkness, this study proposes a multi-feature fusion approach that combines the YOLOv5s-CMBI algorithm for ship exhaust plume detection with the Ringerman Blackness-based grading method. Firstly, diverse datasets are integrated and a subset of the data is subjected to standard optical model aerosolization to form a dataset for ship exhaust plume detection. Subsequently, building upon the YOLOv5s architecture, the CBAM convolutional attention mechanism is incorporated to augment the network’s focus on ship exhaust plume regions while suppressing irrelevant information. Simultaneously, inspired by the BiFPN structure with weighted bidirectional feature pyramids, a lightweight network named Tiny-BiFPN is devised to enable multi-path feature fusion. The Adaptive Spatial Feature Fusion (ASFF) mechanism is introduced to counteract the impact of feature scale disparities. The EIoU_Loss is employed as the localization loss function to enhance both regression accuracy and convergence speed of the model. Lastly, leveraging the k-means clustering algorithm, color information is mined through histogram analysis to determine clustering centers. The Mahalanobis distance is used to compute sample similarity, and the Ringerman Blackness-based method is employed to categorize darkness levels. Ship exhaust plume grades are estimated by computing a weighted average grayscale ratio between the effective exhaust plume region and the background region. Experimental results reveal that the proposed algorithm achieves improvements of approximately 3.8% in detection accuracy, 5.7% in recall rate, and 4.6% in mean average precision (mAP0.5) compared to the original model. The accuracy of ship exhaust plume darkness grading attains 92.1%. The methodology presented in this study holds significant implications for the establishment and application of future ship exhaust plume monitoring mechanisms.

Failure analysis of three-way catalysts through comprehensive characterization and understanding the role of pretreatment - Shiqiang Sun; Chenxi Jin; Wenzhi He; Guangming Li; Haochen Zhu; Juwen Huang (Journal of Environmental Chemical Engineering, 2023)

Comparative life cycle assessment of whiteleg shrimp (Penaeus vannamei) cultured in recirculating aquaculture systems (RAS), biofloc technology (BFT) and higher-place ponds (HPP) farming systems in China - Yue Sun; Haochen Hou; Dengpan Dong; Jiasong Zhang; Xiaohan Yang; Xian Li; Xiefa Song (Aquaculture, 2023)

Enhanced hydroxyl radical generation for micropollutant degradation in the In2O3/Vis-LED process through the addition of periodate - Tao Yang; Linqian An; Ge Zeng; Jiamin Mai; Yuying Li; Jinchuan Lian; Haochen Zhang; Juan Li; Xiaoxiang Cheng; Jianbo Jia; Minchao Liu; Jun Ma (Water Research, 2023)

One-step and real-time detection of Hg2+ in brown rice flour using a biosensor integrated with AC electrothermal enrichment - Haochen Qi; Lei Xiao; Jayne Wu; Li Lv; Xinyu Hu; Youyi Zhuang; Xiaoru Liu; Wenci Zhao; Fangshuo You; Jian Zhang; Lei Zheng (Food Chemistry, 2023)

Cavitation damage inducing the improvement of jet breaking efficiency during hydrate drilling - Xiaoya Wu; Yiqun Zhang; Chengyu Hui; Haochen Huang; Zhaowen Hu; Gensheng Li; Shouceng Tian (Ocean Engineering, 2023)

Remediation of sulfonamides-contaminated groundwater through in-situ activation of peroxymonosulfate by supported hierarchical CuO/MgO nanosheets - Zhuoyue Liu; Lei Ge; Ke Wang; Haochen Yin; Danyang Li; Shengjiong Yang; Gen Wang; Delu Miao (Journal of Water Process Engineering, 2023)

Process and mechanism of enhanced HCl leaching of platinum group metals from waste three-way catalysts by Li2CO3 calcination pretreatment - Shiqiang Sun; Chenxi Jin; Wenting Zhao; Wenzhi He; Guangming Li; Haochen Zhu; Juwen Huang (Journal of Hazardous Materials, 2023)

Targeting of platinum capture under 1+1 aqua regia using robust and recyclable polymeric polyamine resin: Adsorption performance and mechanism - Bohan Li; Wei Xiong; Ying Cao; Xiaoyu Zhou; Haochen Zhu; Min Li; Liming Yang; Penghui Shao (Environmental Research, 2023)

Comparative genomics revealed that Vibrio furnissii and Vibrio fluvialis have mutations in genes related to T6SS1 and T6SS2 - Jiakai Sun; Haochen Su; Wenhui Zhang; Xuesong Luo; Ruichao Li; Ming Liu (Archives of Microbiology, 2023)

A Comprehensive Evaluation Framework of Water-Energy-Food System Coupling Coordination in the Yellow River Basin, China - Dengyu Yin; Haochen Yu; Yanqi Lu; Jian Zhang; Gensheng Li; Xiaoshun Li (Chinese Geographical Science, 2023)

CFSA-AGD: An accurate crosstalk fluorescence spectroscopic decomposition method for identifying and quantifying FDOMs in aquatic environments - Yuchao Fu; Wanxiang Li; Tianyuan Liu; Zhen Zhang; Haochen Li; Jingran Xu; Meizhen Huang (Science of The Total Environment, 2023)

Matching supply and demand for ecosystem services in the Yellow River Basin, China: A perspective of the water-energy-food nexus - Dengyu Yin; Haochen Yu; Yangyang Shi; Mingyue Zhao; Jian Zhang; Xiaoshun Li (Journal of Cleaner Production, 2023)

Meshless Surface Wind Speed Field Reconstruction Based on Machine Learning - Nian Liu; Zhongwei Yan; Xuan Tong; Jiang Jiang; Haochen Li; Jiangjiang Xia; Xiao Lou; Rui Ren; Yi Fang (Advances in Atmospheric Sciences, 2022)

Soil Salinity Estimation Over Coastal Wetlands Based on Random Forest Algorithm and Hydrological Connectivity Metric - Haochen Sui; Dawei Chen; Jiaguo Yan; Bin Li; Wei Li; Baoshan Cui (Frontiers in Marine Science, 2022)
Owing to climate warming and human activities (irrigation and reservoirs), sea level rise and runoff reduction have been threatening the coastal ecosystem by increasing the soil salinity. However, short-term sparse in situ observations limit the study on the response of coastal soil salinity to external stressors and thus its effect on coastal ecosystem. In this study, based on hydrological connectivity metric and random forest algorithm (RF), we develop a coastal soil salinity inversion model with in situ observations and satellite-based datasets. Using Landsat images and ancillary as input variables, we produce a 30-m monthly grid dataset of surface soil salinity over the Yellow River Delta. Based on the cross-validation result with in situ observations, the proposed RF model performs higher accuracy and stability with determination coefficient of 0.89, root mean square error of 1.48 g·kg -1 , and mean absolute error of 1.05 g·kg -1 . The proposed RF model can gain the accuracy improvements of about 11–43% over previous models at different conditions. The spatial distribution and seasonal variabilities of soil salinity is sensitive to the changing signals of runoff, tide, and local precipitation. Combining spatiotemporal collaborative information with the hydrological connectivity metric, we found that the proposed RF model can accurately estimate surface soil salinity, especially in natural reserved regions. The modeling results of surface soil salinity can be significant for exploring the effect of seawater intrusion and runoff reduction to the evolution of coastal salt marsh ecosystems.

Dietary preferences and potential ecological impact on the zooplankton community of Nemopilema nomurai based on stable isotope and fatty acid analyses - Junjian Wang; Chaolun Li; Guang Yang; Zhencheng Tao; Yanqing Wang; Haochen Xian (Journal of Oceanology and Limnology, 2022)

Machine Learning-based Weather Support for the 2022 Winter Olympics - Jiangjiang Xia; Haochen Li; Yanyan Kang; Chen Yu; Lei Ji; Lve Wu; Xiao Lou; Guangxiang Zhu; Zaiwen Wang; Zhongwei Yan; Lizhi Wang; Jiang Zhu; et al. (Advances in Atmospheric Sciences, 2020)

Reclamation of desert land to continuous cotton cropping affects soil properties and microbial communities in the desert-oasis ecotone of Xinjiang, China - Jinbiao Li; Guangming Liu; Jin-Hyeob Kwak; Scott X. Chang; Haochen Gao; Qicong Wu; Jingsong Yang; Jinlin Chen (Journal of Soils and Sediments, 2020)

A Model Output Machine Learning Method for Grid Temperature Forecasts in the Beijing Area - Haochen Li; Chen Yu; Jiangjiang Xia; Yingchun Wang; Jiang Zhu; Pingwen Zhang (Advances in Atmospheric Sciences, 2019)

Life cycle assessment in urban territories: a case study of Dalian city, China - Yu Qi; Yun Zhang; Hui Jiang; Haochen Hou; Jinhua Li (The International Journal of Life Cycle Assessment, 2019)

Life cycle assessment and optimization analysis of different LNG usage scenarios - Yun Zhang; Hui Jiang; Jinhua Li; Shuai Shao; Haochen Hou; Yu Qi; Shushen Zhang (The International Journal of Life Cycle Assessment, 2018)

Generation and management of waste electric vehicle batteries in China - ChengJian Xu; Wenxuan Zhang; Wenzhi He; Guangming Li; Juwen Huang; Haochen Zhu (Environmental Science and Pollution Research, 2017)